2020
DOI: 10.1080/2162402x.2020.1762465
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGF antibodies as surrogate biomarkers of clinical efficacy in stage IIIB/IV non-small-cell lung cancer patients treated with an optimized CIMAvax-EGF vaccination schedule

Abstract: Mazorra (2020) Anti-EGF antibodies as surrogate biomarkers of clinical efficacy in stage IIIB/IV non-small-cell lung cancer patients treated with an optimized CIMAvax-EGF vaccination schedule, OncoImmunology, 9:1, 1762465,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…CIMAvax-EGF has proven to be safe, even after extended use, and capable to keep EGF serum concentration below detectable levels ( 23 , 24 ). The anti-EGF antibody response did not cross-react with other EGFR ligands, such as TGF alpha and amphiregulin ( 22 , 25 ). Notably, in some patients, TGF alpha augmented after 6 months of CIMAvax-EGF, while amphiregulin concentration did not change overtime ( 25 ).…”
Section: Cimavax-egf Immunotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…CIMAvax-EGF has proven to be safe, even after extended use, and capable to keep EGF serum concentration below detectable levels ( 23 , 24 ). The anti-EGF antibody response did not cross-react with other EGFR ligands, such as TGF alpha and amphiregulin ( 22 , 25 ). Notably, in some patients, TGF alpha augmented after 6 months of CIMAvax-EGF, while amphiregulin concentration did not change overtime ( 25 ).…”
Section: Cimavax-egf Immunotherapymentioning
confidence: 97%
“…The anti-EGF antibody response did not cross-react with other EGFR ligands, such as TGF alpha and amphiregulin ( 22 , 25 ). Notably, in some patients, TGF alpha augmented after 6 months of CIMAvax-EGF, while amphiregulin concentration did not change overtime ( 25 ). The increase of one or more ligands after effective EGFR blockade has been reported before ( 26 , 27 ).…”
Section: Cimavax-egf Immunotherapymentioning
confidence: 97%
“…However, a significant OS benefit was observed in a post hoc analysis using Harrington–Fleming test (a weighted log-rank test) in the safety population and was also exhibited among the subgroup of patients who received at least four vaccine doses [28] . An exploratory analysis suggested that the quantity and quality of anti-EGF antibodies were potential biomarkers to predict the efficacy of the CIMAvax-EGF vaccine [29] . No comparison was made between using the CIMAvax-EGF vaccine as a switch maintenance treatment and as a standard maintenance therapy, which made this study less convincing.…”
Section: Promising Strategies Of Immunotherapy In Advanced or Metasta...mentioning
confidence: 99%
“…Unbound labeled antibody is subsequently removed from all wells by washing, and the solution of diethanolamine with substrate para-nitrophenylphosphate is applied to the plate. The enzyme/substrate reaction provokes a yellow color development and absorbance is measured at 405 nm in an ELISA plate reader after stopping of the reaction (13,18).…”
Section: Measurements Of Anti-egf Antibody Titers and Egf Concentrationsmentioning
confidence: 99%